Construction of Bacillus subtilis for efficient production of fengycin from xylose through CRISPR-Cas9 - Yin, Ying; Wang, Pan; Wang, Xin; Wen, Jianping (Frontiers in Microbiology, 2024)
Fengycin is a multifunctional peptide antibiotic produced mainly by Bacillus species and the purpose of this research was to construct a B. subtilis strain that can produce fengycin with the xylose as the substrate with CRSIPR-Cas9. Hence, at the beginning of this study, functional sfp and degQ were expressed in B. subtilis 168 strain to give the strain the ability to produce the fengycin with the titer of 71.21 mg/L. Subsequently, the native promoter PppsA of the cluster responsible for the fengycin synthesis was replaced by the Pveg promoter, resulting in a further 5.22-fold increase in fengycin titer. To confer xylose utilization capacity to B. subtilis, deletion of araR and constitutive overexpression of araE were performed, and the xylose consumption rate of the engineered strain BSUY06 reached 0.29 g/L/h, which is about 6.25-fold higher than that of the parent strain BSUY04-1. In the final phase of this study, the fermentation characteristics were observed and the initial xylose concentration was optimized. In this study, 40 g/L xylose was proved to be the most suitable initial concentration for growth and fengycin fermentation, which leading to a fengycin titer of 430.86 mg/L. This study demonstrated that lignocellulose, the clean and sustainable substrate with xylose as the second largest sugar, is a potential substrate for the production of fengycin.